State of the sector: US worker cooperatives in 2017. Issue 3 (9th December 2019) - Palmer, Tim
Abstract : Purpose: This is a national census of all worker cooperatives in the USA for 2017 implemented by the Democracy at Work Institute which is affiliated with the United States Federation of Worker Cooperatives, the largest worker cooperative association in the USA. The paper aims to discuss these issues. Design/methodology/approach: Longitudinal survey with descriptive analysis of results. Findings: The author identified 394 worker cooperatives and democratic workplaces in all areas of the country in fiscal year 2017 (though early tracking for 2018 shows at least 400 such businesses). While the typical worker cooperative is small (about nine workers and about $588, 600 gross annual revenue) and either recently launched, or converted to the form, there are many notable examples of very large and/or long lasting businesses. Together they employ an estimated 6, 734 workers and produce about $467m in revenue each year. The following analysis attempts to outline the basic geographic, structural, economic and demographic features of these enterprises. Research limitations/implications: The author reached out to this list of businesses via e-mail and telephone contact between August and November 2018. This included both members of the US Federation of Worker Cooperatives and non-members. The author asked participants to provide information based on their fiscal year 2017 performance. The survey asked similar questions to the prior year's survey (e.g. total revenue, total assets, total wages, net income, total workers, total worker–owners, etc.), but also included some small changes in content, format and style. In total, 105 worker cooperatives responded and either fully or substantially completed the survey questions. All non-responsive firms were verified to be in business and operate as worker cooperatives in 2017 to the best of the author's knowledge. Regardless of whether they responded, the author assigned all businesses an industry (NAICS) classification, foundational year and primary location based on basic internet research. This allowed the author to examine the larger universe when analyzing issues around the geography, age and industry of these enterprises. Additionally, internet research also allowed the author to add some other information about a portion of the non-responding worker cooperatives (e.g. number of workers, etc.) when such information was self-reported on their websites. Originality/value: This is the only census of worker cooperatives done in the USA to the author's knowledge.